Optimizing Business Success: The Role of Accounting Information, Business Capital Management, and Response To Environmental Uncertainty - Rita Rosalina; Muhammad Ja’far Shodiq; Khansa Shabihah (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2025)
ABSTRACT This study tests and analyzes the effect of accounting information, working capital management, and environmental uncertainty on business success. This study uses a quantitative approach with primary data obtained through questionnaires. The population in this study consisted of owners or managers of micro, small, and medium enterprises (MSMEs) in Central Java, with a sample size of 405 respondents. The sampling technique used was non-random sampling with a purposive sampling method. Data analysis in this study used multiple linear regression. The results of this study indicate that the use of accounting information, working capital management, and environmental uncertainty have a positive and significant effect on business success. This study contributes theoretically by enriching the literature on business success factors and becoming a reference for further research. These findings help MSMEs manage their businesses and encourage government and financial institution support to increase business competitiveness.Keywords: The Use of Accounting Information, Business Capital Management, Environmental Uncertainty ABSTRAKPenelitian ini bertujuan untuk menguji dan menganalisis pengaruh penggunaan informasi akuntansi, manajeman modal usaha, dan ketidakpastian lingkungan terhadap keberhasilan usaha. Penelitian ini menggunakan pendekatan kuantitatif dengan data primer yang diperoleh melalui penyebaran kuesioner. Populasi dalam penelitian ini adalah pemilik atau pengelola usaha mikro, kecil, dan menengah (UMKM) di Jawa Tengah dengan jumlah sampel sebanyak 405 responden. Teknik pengambilan sampel yang digunakan adalah non random sampling dengan metode purposive sampling. Analisis data dalam penelitian ini menggunakan regresi linier berganda. Hasil penelitian ini menunjukkan bahwa penggunaan informasi akuntansi, manajeman modal kerja, dan ketidakpastian lingkungan berpengaruh positif dan signifikan terhadap keberhasilan usaha. Penelitian ini berkontribusi secara teoritis dengan memperkaya literatur terkait faktor keberhasilan usaha dan menjadi referensi penelitian lanjutan. Praktisnya, temuan ini membantu UMKM dalam mengelola bisnis serta mendorong dukungan pemerintah dan lembaga keuangan untuk meningkatkan daya saing usaha. Kata Kunci: Penggunaan Informasi Akuntansi, Pengelolaan Modal Usaha, Ketidakpastian Lingkungan